2021
DOI: 10.5194/gmd-14-3969-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the offline-coupled GFSv15–FV3–CMAQv5.0.2 in support of the next-generation National Air Quality Forecast Capability over the contiguous United States

Abstract: Abstract. As a candidate for the next-generation National Air Quality Forecast Capability (NAQFC), the meteorological forecast from the Global Forecast System with the new Finite Volume Cube-Sphere dynamical core (GFS–FV3) will be applied to drive the chemical evolution of gases and particles described by the Community Multiscale Air Quality modeling system. CMAQv5.0.2, a historical version of CMAQ, has been coupled with the North American Mesoscale Forecast System (NAM) model in the current operational NAQFC.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Since 2017, there has also been significant efforts at NOAA to use version 15 of FV3GFS (hereafter, GFSv15) rather than NMMB as the meteorological driver for CMAQ in the NAQFC (Huang et al, 2017(Huang et al, , 2018(Huang et al, , 2019. Huang et al (2020) and Chen et al (2021) demonstrated that a version of the GFS-driven CMAQv5.0.2 (GFSv15-CMAQ) forecasting system had partly improved O 3 predictions compared to the NMMB-driven CMAQ (NMMB-CMAQ) system but that the GFSv15-CMAQ had large biases for PM 2.5 that still need improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2017, there has also been significant efforts at NOAA to use version 15 of FV3GFS (hereafter, GFSv15) rather than NMMB as the meteorological driver for CMAQ in the NAQFC (Huang et al, 2017(Huang et al, , 2018(Huang et al, , 2019. Huang et al (2020) and Chen et al (2021) demonstrated that a version of the GFS-driven CMAQv5.0.2 (GFSv15-CMAQ) forecasting system had partly improved O 3 predictions compared to the NMMB-driven CMAQ (NMMB-CMAQ) system but that the GFSv15-CMAQ had large biases for PM 2.5 that still need improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there was an opportunity to simultaneously upgrade and streamline the meteorological coupling between the GFSv16 and a more updated, "stateof-the-science" version of CMAQ at the US EPA (US EPA, 2019; Appel et al, 2021). The current CMAQv5.0.2 used in the NMMB-CMAQ and experimental GFSv15-CMAQ is outdated scientifically with numerous deficiencies, many of which led to the elevated biases and error as described in Huang et al (2017Huang et al ( , 2020 and Chen et al (2021). Hence, there is a need to update the NAQFC to actively developing versions of both FV3GFS and CMAQ.…”
Section: Introductionmentioning
confidence: 99%
“…These virtual points have no error at all, and by introducing the virtual point, the weight value in Equation ( 10) can be reduced. The modified weight for the virtual point n v at the influence radius R is expressed as Equation (12). In Equation (12), as the number of virtual points increases, the distance of the influence of the error at each machine learning prediction point decreases.…”
Section: Hybrid (Cmaq and Rnn-lstm) Modelmentioning
confidence: 99%
“…The modified weight for the virtual point n v at the influence radius R is expressed as Equation (12). In Equation (12), as the number of virtual points increases, the distance of the influence of the error at each machine learning prediction point decreases. In this study, 4 was applied according to Pun's research results for the number of virtual points, and the distance of the radius of influence was 50 km.…”
Section: Hybrid (Cmaq and Rnn-lstm) Modelmentioning
confidence: 99%
See 1 more Smart Citation